Comprehensive cytogenetic and molecular cytogenetic analysis of 44 Burkitt lymphoma cell lines: Secondary chromosomal changes characterization, karyotypic evolution, and comparison with primary samples. Issue 6 (4th March 2014) - Maria Murga Penas, Eva; Schilling, Georgia; Behrmann, Petra; Klokow, Marianne; Vettorazzi, Eik; Bokemeyer, Carsten; Dierlamm, Judith
<x xml:space="preserve">Abstract</x> Burkitt lymphoma cell lines (BL‐CL) are used extensively as in vitro models in genetic studies; however, cytogenetic information is not always available or updated. We provide a comprehensive cytogenetic resource of 44 BL‐CL, assessed by G‐banding, multicolor‐FISH, and FISH with 1q, 3p, 7q, and 13q region‐specific probes, including the first cytogenetic characterization of 22 BL‐CL and the revision of further 22 commonly used BL‐CL. Based on these data, we determined a consensus karyotype, evaluated in detail the secondary chromosomal changes (SCC), and the karyotypic stability of these cell lines. An individual karyotype was identified in all investigated BL‐CL, confirming their unique origin. Most of the BL‐CL remained cytogenetically relative stable after years of intensive cultivation. The most frequent structural SCC were dup(1q), del(13q) and the most frequent numerical SCC were +7, +13. Common breakpoints were located on 1q12, 7q11, and 13q31. The most common gains were in 1q and 7q and the most common losses were in 11q and 13q. Interestingly, the frequency of 1q gains and 13q losses was significantly higher in the EBV‐negative than in the EBV‐positive BL‐CL. Furthermore, by reviewing karyotypes of 221 primary BL listed in the Mitelman database, we observed similarities between BL‐CL and primary BL regarding the frequency of numerical and structural SCC and breakpoint distribution. In BL‐CL and in primary BL two SCC, dup(1q), and +12, always occurred mutually exclusive of each other. These findings validate BL‐CL as appropriate model for in vitro studies on the significance of SCC in the pathogenesis of BL. © 2014 Wiley Periodicals, Inc.